Faktor yang Mempengaruhi Kepatuhan Pasien DM Tipe 2 di Rumah Sakit - Dita Arisa Ratnasari; Nurmainah Nurmainah; Mohammad Andrie (Journal Syifa Sciences and Clinical Research, 2022)
Non-adherence to drug use in patients with diabetes mellitus has an impact on the low clinical impact, risk of complications, low quality of life, and mortality. This study aims to analyze the level of adherence to the use of oral antidiabetic drugs and the factors that influence adherence to the use of antidiabetic drugs in outpatients with type 2 diabetes mellitus in RSUD dr. Rubini, Mempawah Regency. This research is an observational analysis research with a cohort study design. Data collection was carried out retrospectively using medical records of outpatient diabetes mellitus patients from January 2019 to December 2019. The number of samples that met the inclusion and exclusion criteria were 90 patients. Compliance with drug use was measured using the Medication Possession Ratio (MPR) method. Analysis of the relationship between compliance with patient characteristics using the chi square test. The results showed that the characteristics of patients who visited RSUD dr. Rubini tended to be 45 years old (92.2%), female (51.26%), combination therapy regimen (55.6%), uncontrolled blood sugar level (58.9%), and only 12.2% patients who adhere to oral antidiabetic drugs. Chi-square analysis showed that there was no significant relationship between age (p=0.171), gender (p=0.751), therapy regimen (p=0.749) on patient compliance in using antidiabetic drugs. From this study it can be concluded that age, gender, and treatment regimen have no effect on adherence to oral antidiabetic use in patients with type 2 diabetes mellitus.